An Aerial Base Station Assignment Algorithm for 5G Networks - Reis, Renata K. G. dos; L. Damasceno, Maria G.; A. Arnez, Jussif J.; B. de Souza, Caio B.; M. Balieiro, Andson (Anais do Workshop de Redes 6G (W6G), 2025)
Due to network capacity and coverage demands of existing 5G and Beyond 5G networks, Aerial Base Stations (ABS) based on Unmanned Aerial Vehicles (UAV) have been highlighted as a key strategy to expand terrestrial network and assist mobile users. Nevertheless, ABS based on UAV (UAV-BS) are resource constrained in comparison to terrestrial base stations, which implies that resource management procedures are required to efficient UAV-BS operation. In this respect, this work proposes a clustering-based user assignment solution for user to UAV-based ABS, employing a reallocation approach for avoiding connection denial, evaluating the average of allocated users and throughput.